Efeito da utilização de diferentes critérios de controle de qualidade dos genótipos em estudos de associação e seleção genômica ampla - Bresolin, Tiago [UNESP] (2015)
In the genomic selection, the main objective of studies is to estimate the ability or accuracy of genomic prediction. The accuracy of genomic prediction can be influence for the following factors: heritability of the trait, effective population size, maker density, genome, number of loci affecting the trait and distribution of their effects, linkage disequilibrium and number and type of phenotype information used in the statistical analyzes. However, many of this factors described above may be directly or indirectly influenced by the quality control of the makers and, as a consequence, the accuracy of genomic prediction may be affected. For genome-wide association studies, the low quality data can lead to false-negative or positive results in the discovery phase of the regions associated with economic traits. On the other hand, the use of a quality control may remove markers that capture a significant proportion of the genetic variance. Therefore, the objective of this study was evaluate the effect of quality control, density and allele frequency of markers on the genomic selection and the effect of quality control of makers on genome-wide association studies in Nellore breed. Phenotype, genotype and pedigree information, belonging to two breeding programs - DeltaGen and CRV Paint, were used. Age at first calving, weaning weight and yearling weight traits were studied. The animals were genotyped using the Illumina Bovine HD panel which contains 777 thousand SNP markers, approximately. The phenotype was corrected by the fixed effects using a single trait animal model. To the genomic selection were created: 1) three scenarios with different exclusion threshold of SNP markers according to quality control criteria; 2) seven sub panels with different markers density ranging from 10,000 to 734,272 SNP markers; and 3) five bins of markers based on the minor allele frequency. In the genomic selection Genomic ...